The use of learner-generated drawings in the development of music students’ teacher identities - Bennett, Dawn (SAGE publishers, 2013)
Identity development is a continuous process framed within changing social contexts, and is particularly problematic for musicians and other artists whose work contradicts the mythologized image of the artist. The purpose of this article is to examine the professional growth of music students in relation to developing teacher identities. The article reports on the use of learner-generated drawings and journal reflections produced by music performance and education majors; in particular, the article probes students’ perceptions of teaching within a traditional career hierarchy that favours performance and artistic creation above all else. Whilst initial student drawings illustrated traditional images of the teacher as knowledge giver, these gave way to student-centred images in which students appeared to identify with teaching in new ways. The combination of textual and non-textual data provided insights that would not otherwise have been evident, and the consideration of ‘possible selves’ became a useful tool in the explorations of identity and career.